2022
DOI: 10.3389/fpubh.2022.844593
|View full text |Cite
|
Sign up to set email alerts
|

Policy Effects of Ecological Red Lines on Industrial Upgrading and Health Promotion: Evidence From China Based on DID Model

Abstract: The implementation of the Ecological Red Lines (ERL) policy in China is under the background that natural resources have been immoderately exploited for serving rapid economic growth in the last 40 years, where the ecosystem's degradation happened and people's health could be affected. As the secondary industry is the contribution source of rapid growth as well as the threat source that threatens the natural environment and public health, the delimitation of ERL can act as a legal restriction that forces the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…For example, Liu et al (2019) regarded the promulgation of the GCG as a quasi-natural experiment and conducted a DID analysis; they discovered that the debt financing capacity of heavily polluting enterprises is negatively affected by this policy. Ye (2022) conducted an ex-post policy evaluation of the Ecological Red Lines (ERL) policy on the improvements of industrial structure and residents' health based on the DID model and found a positive effect. By referring to Liu et al (2019), this study constructs the DID model used to examine the impact of the green credit policy on firm export quality as follows:…”
Section: Difference-in-difference Modelmentioning
confidence: 99%
“…For example, Liu et al (2019) regarded the promulgation of the GCG as a quasi-natural experiment and conducted a DID analysis; they discovered that the debt financing capacity of heavily polluting enterprises is negatively affected by this policy. Ye (2022) conducted an ex-post policy evaluation of the Ecological Red Lines (ERL) policy on the improvements of industrial structure and residents' health based on the DID model and found a positive effect. By referring to Liu et al (2019), this study constructs the DID model used to examine the impact of the green credit policy on firm export quality as follows:…”
Section: Difference-in-difference Modelmentioning
confidence: 99%
“…Fertilizer is an important input factor in agricultural production, and has made great contributions to improving agricultural production efficiency, ensuring agricultural product supply, and maintaining food security (1,2). However, relevant research shows that the longterm excessive and inefficient application of chemical fertilizer not only leads to the deterioration of the ecological environment in terms of soil compaction, eutrophication of water bodies, and greenhouse gas emissions, but also poses hidden dangers to the quality and safety of agricultural products and human health (3)(4)(5). China is the country with the largest population in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Economic activities are closely related to environmental issues, and economic activities can have good or bad effects on environmental quality, so environmental protection and sustainable development involve all aspects of human economic activities (Yu et al, 2020;Yu et al, 2021;Ye, 2022). The reason why this study chooses the manufacturing sector as the research object of this paper is due to the following considerations.…”
Section: Introductionmentioning
confidence: 99%
“…In October 2021, China issued the "Opinions on Completely Accurately Implementing the New Development Concept and Doing a Good Job in Carbon Neutralization", which put forward the "dual carbon" goal, striving to achieve the peak of carbon dioxide emissions in 2030 and carbon neutrality in 2060 2 . To achieve environmental goals, China has designated several policies, such as natural resource capitalization (Ye et al, 2022), energy intensity constraint policy (Shao et al, 2019) and ecological red line policy (Ye, 2022), etc., including carbon emissions trading (CET) policy.…”
Section: Introductionmentioning
confidence: 99%